Implementation of Pre-Cleaner as An Effort to Preventive Engine Lacks Power Bulldozer D85ess-2 Support Area Rom PT Putra Perkasa Abadi Site Mip Lahat - Fauzi Jatmiko; Panca Nur Hidayat; Joko Triraharjo; Fika Kurniawan; M. Ferry Saputra (Publikasi Indonesia, 2025)
Bulldozer D85ESS-2 operating in the ROM Support Area of PT Putra Perkasa Abadi Site MIP Lahat often experiences engine lacks power problem, which disrupts productivity and increases maintenance costs. This problem is generally caused by air contamination entering the engine system, resulting in decreased combustion efficiency and component damage. This study aims to analyse the effectiveness of pre-cleaner implementation as a preventive measure in overcoming this problem. The method used was a quantitative approach with the collection and analysis of operational data from the D85ESS-2 bulldozer before and after the installation of the pre-cleaner. The data analysed included the frequency of occurrence of the engine lacks power problem, downtime duration, and fuel usage. The results showed that the implementation of a pre-cleaner on the D85ESS-2 bulldozer at PT Putra Perkasa Abadi successfully resolved the problem of engine lacks power by reducing the accumulation of coal dust in the air cleaner. The test results show significant improvements in engine performance, with most parameters meeting the set standards. Thus, the use of a pre-cleaner improves combustion efficiency, reduces maintenance costs, and extends engine life.